2018
DOI: 10.1080/09286586.2018.1546878
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Trachoma Prevalence Survey Covering Seven Districts of Sangha and Likouala Departments, Republic of the Congo

Abstract: Purpose : We set out to estimate the prevalence of trachoma and access to water and sanitation in seven suspected-trachoma-endemic districts of northern Congo, surveyed as a single evaluation unit. Methods : From a complete list of rural villages in the seven districts, we systematically selected 22 with probability proportional to village size. In selected villages, we included all households where there were fewer than 25 in total, or used compact segment sampling to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This study revealed the prevalence of active trachoma PLOS NEGLECTED TROPICAL DISEASES among 1-9 years was 35.37%. This finding is consistent with different studies done in Areka, Zala district, Ethiopia, Nigeria, Chad, Uganda, Central African Republic, and Senegal [23][24][25][26][27][28]. However, this prevalence of active trachoma was found lower compared to different studies conducted in Ankober, Amhara, Amaro, Burji, and Horo Guduru [16,[29][30][31] and higher than different studies conducted in different countries [11,13,14,32].…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed the prevalence of active trachoma PLOS NEGLECTED TROPICAL DISEASES among 1-9 years was 35.37%. This finding is consistent with different studies done in Areka, Zala district, Ethiopia, Nigeria, Chad, Uganda, Central African Republic, and Senegal [23][24][25][26][27][28]. However, this prevalence of active trachoma was found lower compared to different studies conducted in Ankober, Amhara, Amaro, Burji, and Horo Guduru [16,[29][30][31] and higher than different studies conducted in different countries [11,13,14,32].…”
Section: Discussionsupporting
confidence: 90%
“…Even though it was planned to eliminate the disease by the year 2020, finding of this study calls the implementation of A, F, and E components of SAFE are mandatory till the prevalence meets the expected target. Similarly, the overall prevalence is higher than Global Trachoma Mapping Project studies before mass antibiotic initiation began in seven districts of the Republic of the Congo (TF prevalence was 2.5%) and in Benue State, Nigeria (TF prevalence was 0.3% to 5.3%) [35,36]. The later studies done in Congo and Nigeria were done as a baseline survey for mapping the diseases to initiate SAFE interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, trachoma was not considered endemic in the RoC [ 114 ], despite the Likouala department bordering areas of high trachoma prevalence in the CAR [ 115 ]. The only trachoma survey in the RoC, conducted in 2015 by the PNLO, aimed at assessing the prevalence of trachomatous inflammation-follicular (TF) in children aged 1–9 years and trachomatous trichiasis (TT) in adults aged ≥15 years in two ADs of the Sangha department and five ADs of the Likouala department [ 116 ]. When considering these seven districts as a single assessment unit, the prevalence of TF was 2.5%, and no case of TT was reported.…”
Section: Resultsmentioning
confidence: 99%